2018
DOI: 10.1253/circj.cj-17-1213
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Figure-of-Eight Suture for Hemostasis After Radiofrequency Catheter Ablation for Atrial Fibrillation

Abstract: Background: This study evaluated the safety and efficacy of venous figure-of-eight (FoE) suture to achieve femoral venous hemostasis after radiofrequency (RF) catheter ablation (CA) for atrial fibrillation (AF). Methods and Results:We retrospectively examined 517 consecutive patients undergoing RFCA for AF. The control group (n=247) underwent manual compression for femoral venous hemostasis after sheath removal with 6 h of bed rest. The FoE group (n=270) underwent FoE suture technique with 4 h of bed rest. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 14 publications
0
23
1
Order By: Relevance
“…Nine studies were found to be eligible based on the inclusion criteria. [4][5][6][8][9][10][11][12][13]…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies were found to be eligible based on the inclusion criteria. [4][5][6][8][9][10][11][12][13]…”
Section: Search Resultsmentioning
confidence: 99%
“…A total of 121 citations were identified after an intensive search process, 23 articles were assessed for eligibility, and 14 were excluded after screening. Nine studies were found to be eligible based on the inclusion criteria 4‐6,8–13 …”
Section: Resultsmentioning
confidence: 99%
“…6,14,15 The FOE suture can reduce the risk of rebleeding, shorten the duration of bed rest and relieve patient discomfort. 6,15 When used for haemostasis following intervention via the femoral vein, the suture silks are placed in the site before removal of the catheter or catheter sheaths. 6 Considering the high risk of bleeding from the femoral artery, the FOE suture was inserted after removing the catheter or catheter sheaths and closing the femoral artery access site in this current study.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective and nonrandomized studies have demonstrated the safety of the figure‐of‐eight suture for hemostasis 8 . The largest published study, which was not randomized, included 512 patients undergoing radiofrequency catheter ablation of AF . These investigators demonstrated that use of the figure‐of‐eight suture was associated with a lower risk of rebleeding, shorter recovery times, and improved patient comfort.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The largest published study, which was not randomized, included 512 patients undergoing radiofrequency catheter ablation of AF. 8 These investigators demonstrated that use of the figure-of-eight suture was associated with a lower risk of rebleeding, shorter recovery times, and improved patient comfort. Similar findings have been observed in other nonrandomized trials for patients undergoing cryoballoon ablation for AF, which requires a larger venous sheath than utilized for radiofrequency ablation for AF.…”
Section: Previous Studiesmentioning
confidence: 99%